Safety evaluation of an extension of use of the food enzyme triacylglycerol lipase from the genetically modified Aspergillus niger strain LFS - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme triacylglycerol lipase (triacylglycerol acylhydrolase, EC 3.1.1.3) is produced with the genetically modified Aspergillus niger strain LFS by DSM Food Specialties B.V. A safety evaluation of this food enzyme was made previously, in which EFSA concluded that this food enzyme did not give rise to safety concerns when used in one food manufacturing process. Subsequently, the applicant has requested to extend its use to include one additional process. In this assessment, EFSA updated the safety evaluation of this food enzyme when used in a total of two food manufacturing processes. The dietary exposure was calculated to be up to 0.110 mg total organic solids (TOS)/kg body weight (bw) per day in European populations. When combined with the no observed adverse effect level previously reported (1038 mg TOS/kg bw per day, the highest dose tested), the Panel derived a margin of exposure of at least 9436. Based on the new data, the revised margin of exposure and the previous evaluation, the Panel concluded that this food enzyme does not give rise to safety concerns under the revised intended conditions of use.